Cystatin C and uncontrolled hypertension - Omaygenç, Mehmet Onur; Özcan, Özgür Ulaş; Çakal, Beytullah; Karaca, Oğuz (Turkish Society of Cardiology, 2020)
Objective: Increased serum level of cystatin C, a sensitive biomarker for renal function, seems to predict adverse cardiovascular events. We investigated the predictive value of serum cystatin C for controlling hypertension in an observational study.Methods: We screened 1037 adults residing in both rural and urban communities. They were grouped based on their diagnosis and control of hypertension.Results: Serum cystatin C levels in patients with uncontrolled hypertension were higher than those in patients with controlled hypertension (0.98 +/- 0.23 mg/L vs. 0.89 +/- 0.19 mg/L, p=0.001). However, serum creatinine levels were similar between these groups (0.72 +/- 0.20 mg/dL vs. 0.70 +/- 0.18 mg/dL, p=0.89). Serum cystatin C levels increased the probability of uncontrolled hypertension independent from confounding factors (odds ratio, 1.48; 95% confidence interval, 1.09-5.64; p=0.03).Conclusion: Subtle kidney dysfunction may be detected using serum cystatin C concentrations among patients with poor blood pressure control and normal serum creatinine levels.
Keywords: Chronic Kidney Disease; Creatinine; Cystatin C; Hypertension